Increased expression of HERG K+ channels contributes to myelodysplastic syndrome progression and displays correlation with prognosis stratification. Issue 10 (25th November 2016) - Lu, Li; Du, Wen; Liu, Wei; Guo, Dongmei; He, Xiaoqi; Li, Huiyu
Abstract : Objectives : Human ether-a-go-go-related gene ( HERG ) K + channels are shown to be aberrantly expressed in a variety of cancer cells where they play roles in contributing to cancer progression. Myelodysplastic syndromes (MDS) are a group of clinical heterogeneous disorders characterized by bone marrow failure and dysplasia of blood cells. However, the involvement of HERG K + channels in MDS development is poorly understood. Methods : The expression of HERG K + channels in untreated MDS, acute myeloid leukemia (AML) patients and the control group was detected by flow cytometry. The roles of HERG K + channels in regulation of SKM-1 cell proliferation, apoptosis, and cell cycle were determined by CCK-8 assay and flow cytometry, respectively. Results : We found that expression of HERG K + channels in MDS patients was significantly higher than controls and was lower than AML. Percentage of HERG K + channels on CD34+CD38− cells gradually increased from controls to high-grade MDS subtypes. And HERG K + channel levels showed an ascending tendency from low-risk to high-risk MDS group. In addition, the CCK-8 assay, apoptosis and cell cycle analysis were performed and showed that blockage of HERG K + channels decreased the proliferation of MDS cells but rarely had effects on cell apoptosis and cell cycle distribution. Conclusion : Our study demonstrated that HERG K + channels might be a potential tumor marker of MDS. These channels were likely to contribute to MDS progression and were helpful for predicting prognosis of MDS. Inhibition of HERG K + channels might be a novel therapeutic measure for MDS.